“PASCA LISAN”, A DADAIST FILM WITH TRISIKON - Sito Fossy Biosa; Waret Khunacharoensap (Institut Seni Indonesia Surakarta, 2022)
Time-based art, often known as dynamic art, is becoming increasingly popular since the artsy community finds realistic action movies monotonous. In this respect, the Dadaist Film movement is crucial as a part of the dynamics of the non- compartmentalized art. The intimacy of the artistic production and manipulation process of the Dada movement encouraged me to apply the TRISIKON (Three Situations and Conditions) idea to make the Dada movement-inspired film